2006
DOI: 10.2307/4134576
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exposure to Bacteria on Metabolism in the Penaeid ShrimpLitopenaeus vannamei

Abstract: We hypothesized that aggregation of bacteria and hemocytes at the gill, which occurs as part of the shrimp's antibacterial immune defenses, would impair normal respiratory function and thereby disrupt aerobic metabolism. Changes in oxygen uptake and lactate accumulation were determined in Litopenaeus vannamei, the Pacific white shrimp, following injection with either saline (control) or a strain of the gram-negative bacterium Vibrio campbellii that is pathogenic in crustaceans. The rate of oxygen uptake was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 25 publications
6
22
0
Order By: Relevance
“…These results are similar to those of Scholnick et al (Scholnick et al, 2006) who found that the shrimp L. vannamei experienced a 27% reduction in oxygen uptake 4h after injection of V. campbellii, which declined 24h later to 40%. Reduction of aerobic metabolism is accompanied by a small, but significant, increase in anaerobic metabolism as indicated by elevated hemolymph lactate levels (Fig.3).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…These results are similar to those of Scholnick et al (Scholnick et al, 2006) who found that the shrimp L. vannamei experienced a 27% reduction in oxygen uptake 4h after injection of V. campbellii, which declined 24h later to 40%. Reduction of aerobic metabolism is accompanied by a small, but significant, increase in anaerobic metabolism as indicated by elevated hemolymph lactate levels (Fig.3).…”
Section: Discussionsupporting
confidence: 82%
“…It is possible that these small lactate changes could be indirect results of changes in hemolymph pH (not measured) which may alter the dynamic equilibrium between lactate and pyruvate. The result is an overall metabolic depression similar to the one observed in the Pacific white shrimp (Scholnick et al, 2006).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The hemocytes recognize and remove these foreign matters which become trapped in the gills, what might result in a decline in the respiration (Martin et al, 2000;Smith and Ratcliffe, 1980;White and Ratcliffe, 1982). Accordingly, in the Atlantic blue crab Callinectes sapidus and in the whiteleg shrimp Litopenaeus vannamei the infection with the bacterial pathogen Vibrio campbellii, impaired the respiration function and a metabolic depression of > 30% was observed Scholnick et al, 2006;Thibodeaux et al, 2009). The present and recent studies show, that a strong immune response and a protective function of the gill against invading pathogens might lead to an impairment of the respiratory function, probably due to these aggregated hemocytes that inhibit the lamellas of the gills.…”
Section: Discussionmentioning
confidence: 99%